2021
DOI: 10.1039/d1ra06697h
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of apoptosis based on fluorescence lifetime imaging microscopy with a mitochondria-targeted viscosity probe

Abstract: Here we designed a mitochondria-targeted two-photon viscosity probe (TPA-Mit), which sensitively responds to viscosity variations with fluorescence lifetime changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is demonstrated that the lifetime of Biotin‐V can be used to monitor viscosity in mitochondrial. In addition, Liu's group designed another viscosity probe based on two‐photon (TPA‐Mit), as shown in Figure 6b [44] . Using the TPA‐Mit probe, it could be detected that after SKOV‐3 cells were induced to apoptosis by paclitaxel (PTX), the fluorescence lifetime of TPA‐Mit was increased.…”
Section: Applications Of Lifetime‐based Responsive Probes In Biologic...mentioning
confidence: 99%
See 3 more Smart Citations
“…It is demonstrated that the lifetime of Biotin‐V can be used to monitor viscosity in mitochondrial. In addition, Liu's group designed another viscosity probe based on two‐photon (TPA‐Mit), as shown in Figure 6b [44] . Using the TPA‐Mit probe, it could be detected that after SKOV‐3 cells were induced to apoptosis by paclitaxel (PTX), the fluorescence lifetime of TPA‐Mit was increased.…”
Section: Applications Of Lifetime‐based Responsive Probes In Biologic...mentioning
confidence: 99%
“…(b) Chemical structures of TPA‐Mit and FLIM images of cells incubated with PTX at different times Scale bar: 10 μm. Reproduced with permission [44] . Copyright 2021, The Royal Society of Chemistry.…”
Section: Applications Of Lifetime‐based Responsive Probes In Biologic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiphoton fluorescence lifetime imaging microscopy (FLIM) is considered to be an excellent alternative to traditional fluorescence imaging, which could effectively eliminate short-lived background fluorescence and provide fluorescence images with a high signal-to-noise ratio. So far, multiphoton FLIM imaging agents are mostly organometallic complexes containing heavy metals such as europium, ruthenium, and iridium . These complexes with long excited-state lifetimes are expensive and even potentially toxic, which severely limits their biological applications.…”
mentioning
confidence: 99%